Approach to the Assessment and Management of Adult Patients With Atopic Dermatitis: A Consensus Document. Section IV: Treatment Options for the Management of Atopic Dermatitis. Issue 1 (November 2018) - Dhadwal, Gurbir; Albrecht, Lorne; Gniadecki, Robert; Poulin, Yves; Yeung, Jensen; Hong, Chih-ho; Gooderham, Melinda J.
The objectives of therapy for atopic dermatitis (AD) are to reduce skin inflammation and pruritus, restore skin barrier function, and improve quality of life (QoL). Treatments can be classified as moisturizing and basic care, topical therapy, phototherapy, and systemic therapy. In this review, we summarize the treatments for AD and recommendations for their use.